O ROLI PRAWA RZYMSKIEGO W DAWNEJ RZECZYPOSPOLITEJ W ŚWIETLE „KURSU PRAWA CYWILNEGO POLSKIEGO” ALEKSANDRA MICKIEWICZA Z 1829 ROKU - Godek, Sławomir (Zeszyty Prawnicze, 2016)
Roman Law in Poland-Lithuania in the Light of Aleksander Mickiewicz’s 1829 Lecture on Polish Civil Law Summary The Polish Academy of Sciences library collection at Kórnik holds a manuscript with a lecture on Polish civil law and its history delivered by Aleksander Mickiewicz in 1829 at Krzemieniec School. This lecture provides us with a general idea of Mickiewicz’s views on the impact of Roman law on the development of Polish legal culture. Mickiewicz was rather critical of the views of Tadeusz Czacki, who had argued that Polish law was derived from Scandinavian law. Mickiewicz believed that Polish law under the early kings and princes of the Piast dynasty was a native creation, though subject to limited influence from Roman and German law. He held that Roman law originally came to Poland through canon law, but its influence was superficial. It was manifest in proceedings in the royal courts and in the borrowing of certain terms, which were sometimes used to designate purely indigenous legal institutions. This was also true of the usage of Roman terminology in Polish medieval chronicles. Mickiewicz saw the Roman elements in the 14th-century Statutes of Casimir the Great as an erudite display by their authors or as later additions to the original collection. Mickiewicz also devoted much attention to Lithuanian law. In particular, he showed that the Lithuanian Statutes were subject to the influence of many foreign systems of law including a number of elements borrowed from Roman law (wills, disinheritance, the penalty for parricide). Mickiewicz was convinced that Roman law appeared in the Grand Duchy at the same time as German law, and in connection with Lithuanian peregrinations for study abroad.